A comprehensive evaluation of PM2.5-bound PAHs and their derivative in winter from six megacities in China: Insight the source-dependent health risk and secondary reactions. (July 2022) - Sun, Jian; Shen, Zhenxing; Zhang, Tian; Kong, Shaofei; Zhang, Hongai; Zhang, Qian; Niu, Xinyi; Huang, Shasha; Xu, Hongmei; Ho, Kin-Fai; Cao, Junji
Graphical abstract: Abstract: Atmospheric PAHs (polycyclic aromatic hydrocarbons) and their derivatives are a global concern that influences environments and threatens human health. Concentrations of 52 PAHs and the main derivatives in six Chinese megacities were measured in the winter of 2019. The concentrations of ∑PAHs (sum of 52 PAHs) ranged from 19.42 ± 7.68 to 65.40 ± 29.84 ng m −3, with significantly higher levels in northern cities (Harbin [HB], Beijing [BJ], and Xi'an [XA]) than southern ones (Wuhan [WH], Chengdu [CD] and Guangzhou [GZ]). Source apportionment of ∑PAHs was conducted by the PMF model and results showed coal combustion and traffic emissions were the two dominant sources, which dominated ∑PAHs in northern and southern cities, respectively. Biomass burning was also characterized as a crucial source of ∑PAHs and showed extremely high contributions in XA (42.5%). Assisted by the individual PAH source apportionment results, the source-depend TEQ (total BaP equivalent) and incremental lifetime cancer risk (ILCR) were firstly reported in these cities. The results highlighted the contributions of coal combustion and biomass burning to both TEQ and ILCR, which were underestimated by ∑PAHs source apportionment. Secondary organic aerosol-derived PAHs were demonstrated to increase the TEQ compared with the fresh PAHs and three parameters, namely temperature, relative humidity, and O3 concentrations were characterized by multiple linear regression as the principal factors influencing secondary reactions of PAHs in winter. This study provides accurate human health-orientated results and potential control measures to mitigate the toxicity of secondary formed PAHs, and significantly decrease the uncertainty level of traditional methods. The results also revealed great progress in air pollution control by the Chinese government in the past 20 years, but still a long way to go to formulate strict emission control strategies from both environmental and human health-protective perspectives.